GERAKAN AHMADIAH (QADIANI) DI MALAYSIA: SATU SOROTAN SEJARAH - Mohamed Dali, Azharudin (Journal of Al-Tamaddun, 2010)
This paper outlines the development of the Ahmadiya movement, better known as the Qadianis in Malaysia. This movement was categorised as a deviant group, but until today, it still exists and in Malaysia, it has around 1500 adherents. This study will trace the development of this movement, in three parts. The first part would be the origins of the movement in India and its founder, Mirza Ghulam Ahmad, the second part the real and purported reasons of the Ahmadiya movement, and the third part, its mission in Malaysia. This paper will also look into a few questions regarding its existence and its ability to survive in this country.